Gulf War Veterans with Psychiatric Symptoms (Anxiety, Depression, and PTSD) Significantly Improve on a Low Glutamate Diet. (29th May 2020) - Brandley, Elizabeth; Kirkland, Anna; Holton, Kathleen
Abstract: Objectives: The objective of this study was to assess the effects of a low glutamate dietary intervention on measures of anxiety, depression, and PTSD in veterans with Gulf War Illness (GWI). Methods: Forty Gulf War veterans were recruited from across the U.S. for a clinical trial examining the effects of a low glutamate diet on symptoms of GWI. During baseline testing, subjects completed the GAD-7 anxiety measure, the PCL-C PTSD scale, and the Center for Epidemiologic Studies Depression Scale (CES-D), and then were randomized to immediate dietary intervention or a wait-listed control group. All participants received intensive dietary training before starting the diet. After one month on the diet, post-diet testing was completed, then subjects were randomized into a double-blind, placebo-controlled crossover challenge with MSG/placebo to test for a return of symptoms. The challenge data has not yet been un-blinded; therefore, it will not be discussed in this abstract. Pre-post diet change scores were analyzed using the Wilcoxon Signed Rank tests via SPSS ® v26. Results: Results demonstrate highly significant improvements in psychiatric symptoms associated with GWI after one-month on a low glutamate diet. Scores were reduced from a median (IQ range) of 9(13) to 4(8), P  = 0.001 for anxiety; from 27(15) to 19(10), P  < 0.001 for depression; and from 57(32) to 39(32), P  < 0.001 for PTSD. Conclusions: These results suggest that a low glutamate diet may improve depression, anxiety, and PTSD in veterans with GWI. Future analysis of the double-blind, placebo-controlled crossover challenge data will provide a better understanding of whether challenge with glutamate can significantly increase anxiety, depression and PTSD relative to placebo. Funding Sources: The US Army Medical Research Acquisition Activity, 820 Chandler St, Fort Detrick MD 21, 702–5014 is the awarding and administering acquisition office. This work is supported by the Office of the Assistant Secretary of Defense for Health Affairs through the Gulf War Illness Research Program. Opinions, interpretations, conclusions and recommendations are those of the author and are not necessarily endorsed by the Department of Defense.